2016
DOI: 10.21443/1560-9278-2016-1/2-268-277
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dynamics of hydrological conditions of the Zelenetskaya Bay, East Murman

Abstract: Long-term dynamics of hydrological conditions of the Zelenetskaya Bay, East MurmanАннотация. Исследованы черты океанографического режима губы Зеленецкая. Это одна из губ Восточного Мурмана, исторически занимает важное место в хозяйственном освоении Кольского прибрежья и в создании форпоста академической науки в Западной Арктике. Обобщены данные многолетних наблюдений и представлены среднемноголетние параметры метеорологических и гидрологических характеристик этого водоема за последнее десятилетие. Представленн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Mean depth is 7 m. Depth range in adjacent sea areas considered in this study is 30-40 m. High tidal levels (3-4 m) ensure intensive water exchange between the inner part of Dalnezelenetskaya Bay and the open sea. According to 2002-2012 data, temperature minimum in the upper water layer (surface) occurs in February (0.7 • C) and the maximum in August (9.7 • C) although in some years the maximum could be observed in July (Il'in et al, 2016). The lowest salinity level (32.2 psu) is usually registered in May and associated with high input of melt water.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Mean depth is 7 m. Depth range in adjacent sea areas considered in this study is 30-40 m. High tidal levels (3-4 m) ensure intensive water exchange between the inner part of Dalnezelenetskaya Bay and the open sea. According to 2002-2012 data, temperature minimum in the upper water layer (surface) occurs in February (0.7 • C) and the maximum in August (9.7 • C) although in some years the maximum could be observed in July (Il'in et al, 2016). The lowest salinity level (32.2 psu) is usually registered in May and associated with high input of melt water.…”
Section: Study Areamentioning
confidence: 99%
“…The lowest salinity level (32.2 psu) is usually registered in May and associated with high input of melt water. In autumn and winter, salinity is stabilized at a level of 34 psu (Il'in et al, 2016). The minimum level of dissolve oxygen is registered in December (94%), the maximum in May (124%) (Dvoretsky and Dvoretsky, in press).…”
Section: Study Areamentioning
confidence: 99%
“…The hydrological regime at the study sites did not differ from that observed in 2004-2007 [12]. According to literature data, there was a slight increase in water temperature in the coastal regions of the Kola Peninsula [13]. In 1983-1984, the water temperature in the 0-15-m layer in January could drop below -1.5°C, in June-July, it was stably below 7°C and reached 9°C only at the end of August-September.…”
Section: Hydrological Regimementioning
confidence: 49%
“…In 1983-1984, the water temperature in the 0-15-m layer in January could drop below -1.5°C, in June-July, it was stably below 7°C and reached 9°C only at the end of August-September. In 2002-2012, the average surface water temperature was 3.8°С, in July-September, it exceeds 7°С in average, while in winter it did not fall below 0.7°С [13].…”
Section: Hydrological Regimementioning
confidence: 93%
“…Seasonal oceanographic fluctuations in Dalnezelenetskay Bay (modified from Kuznetsov & Schoschina 2003; Il'in et al 2016). …”
Section: Gonad Enhancement Of Sea Urchins Reared In a Running‐water Smentioning
confidence: 99%